Peripheral artery disease, abnormal ankle-brachial index, and prognosis in patients with acute coronary syndrome - Berkovitch, Anat; Iakobishvili, Zaza; Fuchs, Shmulik; Atar, Shaul; Braver, Omri; Eisen, Alon; Glikson, Michael; Beigel, Roy; Matetzky, Shlomi (Frontiers in Cardiovascular Medicine, 2022)
Objectives Ankle-brachial index (ABI) is an independent prognostic marker of cardiovascular events among patients with coronary artery disease (CAD). We aimed to investigate the outcome of patients hospitalized with acute coronary syndrome (ACS) and abnormal ABI. Approach and results ABI was prospectively measured in 1,047 patients hospitalized due to ACS, who were stratified into three groups, namely, those with clinical peripheral artery disease (PAD) (N = 132), those without clinical PAD but with abnormal (< 0.9) ABI (subclinical PAD; N = 148), and those without clinical PAD with normal ABI (no PAD; N = 767). Patients were prospectively followed for 30-day major adverse cardiovascular event (MACE) and 1-year all-cause mortality. The mean age was 64 years. There was a significant gradual increase throughout the three groups in age, i.e., the incidence of prior stroke, diabetes mellitus, and hypertension (p for trend = 0.001 for all). The in-hospital course showed a gradual rise in the incidence of complications with an increase in heart failure [2.5, 6.1, and 9.2%, (p for trend = 0.001)] and acute kidney injury [2, 4.1, and 11.5%, (p for trend = 0.001)]. At day 30, there was a stepwise increase in MACE, such that patients without PAD had the lowest rate, followed by subclinical and clinical PADs (3.5, 6.8, and 8.1%, respectively, p for trend = 0.009). Similarly, there was a significant increase in 1-year mortality from 3.4% in patients without PAD, through 6.8% in those with subclinical PAD, to 15.2% in those with clinical PAD (p for trend = 0.001). Conclusion Subclinical PAD is associated with poor outcomes in patients with ACS, suggesting that routine ABI screening could carry important prognostic significance in these patients regardless of PAD symptoms.